The child psychotherapists' role in consultation work with the professional network around looked after children. Issue 3 (2nd July 2020) - Robinson, Fiona; Luyten, Patrick; Midgley, Nick
ABSTRACT: Consultation with the network around a child is a core aspect of a child psychotherapist's role; however, little has been written about this aspect of their work with looked after children. Aims: To gain an understanding of child psychotherapists' work with the network around looked after children, and what they see as specific to the psychoanalytic approach. Methods: Nine participants with expertise in working with foster carers and looked after children's professionals, participated in in-depth interviews. Results: Thematic analysis identified three themes concerned with the tensions child psychotherapists hold within themselves whilst consulting to the network around looked after children. The first theme encapsulates participants' sense of dilemma between what they felt was demanded of them versus what they could offer. The second theme describes participants' sense of tensions around the way the system is organised versus what they felt is in the best interests of the child and network. The third theme captures participants' views about whether their consultant role fits a generic model of reflective practice similar to that offered by professionals from other disciplines, or whether the psychoanalytic approach brings something distinctive to this model of consultation. Links to existing theory and practice implications are discussed.